Zinc supplementation leads to immune modulation and improved survival in a juvenile model of murine sepsis. Issue 1 (January 2017) - Ganatra, Hammad A; Varisco, Brian M; Harmon, Kelli; Lahni, Patrick; Opoka, Amy; Wong, Hector R
Children with severe sepsis are known to have altered zinc homeostasis and decreased circulating zinc levels, suggesting a role for zinc supplementation to improve outcomes. We tested the hypothesis that zinc supplementation would improve survival in a juvenile model of polymicrobial sepsis. Juvenile (13–14-d-old) C57BL/6 mice were treated with 10 mg/kg of zinc via i.p. injections (or vehicle) for 3 d prior to induction of polymicrobial sepsis via i.p. cecal slurry injections. Survival after sepsis was followed for 3 d, and bacterial clearance, ex vivo phagocytosis, systemic inflammatory markers and neutrophil extracellular trap (NET) formation were quantified. We found a significant survival benefit and decreased bacterial burden among zinc supplemented mice when compared with the control group. Zinc supplementation also resulted in enhanced phagocytic activity, greater neutrophil recruitment in the peritoneal cavity and NET formation, suggesting a possible mechanism for improved bacterial clearance and survival. We also noted decreased serum cytokine levels and decreased myeloperoxidase activity in lung tissue following zinc supplementation, suggesting attenuation of the systemic inflammatory response. In conclusion, zinc supplementation improves bacterial clearance, and hence survival, in juvenile mice with polymicrobial sepsis.